2012
DOI: 10.12659/msm.883351
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory pressures and expiratory peak flow rate of patients undergoing coronary artery bypass graft surgery

Abstract: SummaryBackgroundTo evaluate clinical and laboratorial parameters that predict decreased respiratory function in patients subjected to coronary artery bypass graft surgery (CABG).Material/MethodsThis was a prospective study evaluating 61 patients subjected to CABG with cardiopulmonary bypass, median sternotomy, and under mechanical ventilation for up to 24 h. One day before surgery, clinical information was recorded. Maximal inspiratory (MIP) and expiratory (MEP) pressures, and expiratory peak flow rate (EPFR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
1
2
0
1
Order By: Relevance
“…The finding of this study was showed the correlation of MIP and MEP alteration with the change in PEF indicates that decreased the respiratory muscle strength after open-heart surgery was associated with the attenuated of cough ability. In our results, respiratory muscle strength and PEF were significantly reduced in the post-operative period, which is similar to a study by Gimenes et al (14). These reductions are related to intra-operative factors such as surgical manipulation, anesthesia, cardioplegic agents, thermal damage, cardiopulmonary bypass, and mechanical ventilation used.…”
Section: Discussionsupporting
confidence: 91%
“…The finding of this study was showed the correlation of MIP and MEP alteration with the change in PEF indicates that decreased the respiratory muscle strength after open-heart surgery was associated with the attenuated of cough ability. In our results, respiratory muscle strength and PEF were significantly reduced in the post-operative period, which is similar to a study by Gimenes et al (14). These reductions are related to intra-operative factors such as surgical manipulation, anesthesia, cardioplegic agents, thermal damage, cardiopulmonary bypass, and mechanical ventilation used.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, angina can lead to pulmonary changes together with COPD. Gimenes C et al [ 16 ] observed that severe angina (class III), in association with COPD, results in higher reductions in pulmonary pressures between the preoperative period and the 5th postoperative day. The above-mentioned reasons can cause obstructive and restrictive ventilation disorder, and decrease vital capacity and maximal ventilation volume.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with heart disease often have respiratory changes. The associated comorbidities, the loss of respiratory muscle strength, the instability of the chest, the inflammatory process triggered by external factors, such as the CEC, directly affect the individual's lung capacity during this period 27 .…”
Section: Resultsmentioning
confidence: 99%